A case of elephantiasis neuromatosa - K, Gunasekaran; S, Sivakumar; K, Thiruvarutchelvan (Indian Journal of Child Health, 2018)
Elephantiasis neuromatosa (EN) is a rare and unique complication of plexiform neurofibroma, a type of neurofibromatosis type 1, and manifests as hypertrophy of an extremity (either lower limb or upper limb). EN can be seen in individuals of any age group including children and young adults where males and females are affected equally. Diagnosis is done primarily by magnetic resonance imaging of the affected region along with a history and clinical examination. EN may lead to severe functional impairment of the involved limb with cosmetic disfigurement. Treatment is mainly surgical with less satisfactory results. Here, we present a 6-year-old child with EN.